A breath of fresh air: french books in the Catalogues of the 18th century of the bookshop Mallén of Valencia - Bas Martín, Nicolás (Revista General de Información y Documentación, 2013)
The Catalogues of books constitute close to the auctions of books and the inventories of libraries the most important sources for the study of the world of the book during the 18th century. Through the study of French books from the catalogues of the family booksellers’ Mallén of Valencia it is tried to know the authors and works that circulated in the city, besides the circuits, suppliers and clients of such a trade. A business that helped to modernize the cultural and political structures of the moment.